Intravenous Immunoglobulin Treatment Did Not Improve Tics in a Patient With Gilles de la Tourette Syndrome and Intrathecal Antibody Synthesis - Szejko, Natalia; Fremer, Carolin; Sühs, Kurt-Wolfram; Macul Ferreira de Barros, Pedro; Müller-Vahl, Kirsten R. (Frontiers in Neurology, 2020)
Gilles de la Tourette syndrome (GTS) is a neuropsychiatric disorder characterized by motor and vocal tics. There are several hypotheses as to the cause of the disease. One of which suggests that the immune system is involved in the pathophysiology of GTS. Here, we present a 40 years old female patient with a typical history and clinical presentation of GTS with tics and psychiatric comorbidities, in whom positive oligoclonal bands (OCB) type 2 in cerebral spinal fluid (CSF) were detected in an earlier study. At that time point, all other investigations were unremarkable (including neurological examination and cMRI), but 2 years later later, she presented with further neurological symptoms including tetraparesis mostly affecting the left limbs, distal hypesthesia and paresthesia, and dyspnea. Since further examinations (including EMG, MRI, CSF, virological and bacteriological tests as well as autoimmune-encephalitis antibodies) revealed normal results, based on clinical presentation, the diagnosis of Guillain-Barré-like immune-mediated neuropathy was made and treatment with intravenous immunoglobulins (IVIg) (30g/day for 5 days) was initiated resulting in complete remission of immune-mediated neuropathy. Based on the “immune hypothesis” of GTS, we were interested in whether in this patient positive CSF OCBs might serve as a biomarker for treatment response of tics and additional GTS related psychiatric symptoms to IVIg, and therefore assessed tics, premonitory urges and psychiatric comorbidities before and several times after IVIg treatment. However, even though immune-mediated neuropathy resolved after treatment, tics, premonitory urges and comorbidities remained unchanged. Thus, this case study suggests that treatment with IVIg is not effective in the treatment of GTS - even in a patient with intrathecal antibody synthesis as expressed by CSF isolated OCBs.